Morbidity and mortality profiles and outcomes of neonates admitted in the special newborn care unit of tertiary care hospital of Government Medical College Rajouri of district Rajouri of union territory of Jammu and Kashmir: a hospital-based study - Iqbal, Javaid; Sharma, Sudekshan; Naaz, Balqies (International Journal of Research in Medical Sciences, 2023)
Background: Neonatal deaths constitute major portion of under-five mortalities in India. Neonatal period is very important and precious period because most of the preventable morbidities and mortalities occur in this period. In our country, prematurity, infection and prenatal asphyxia are three major causes for neonatal mortality. Various special newborn care unit (SNCU) are established in different district Hospitals to provide neonatal care which further decrease neonatal mortality. Methods: This observational retrospective study was planned to determine the clinical profile and outcome of various neonatal admissions at SNCU, of department of paediatrics Government Medical College Rajouri, Jammu and Kashmir a newly established medical college in the rural setting of northern India which is a tertiary care hospital. The data was collected for a period of 1 year from 01 April 2021 to 31 March 2022. Detailed information was collected from files and registered onto the preset proformas and results were compiled. Results: A total 2495 newborns were enrolled for the study. 1796 (71.98%) were inborn and 699 (28.01%) were out born. Total male babies were 1569 (62.88%) and female babies were 926 (37.12%). Majority of patients were full term and weight ≥2.5 kg (86.05%). major indications for admission were sepsis 557 (22.32%), prenatal asphyxia 532(21.32%), neonatal hyperbilirubinemia 387 (15.5%), Low birth weight 348 (13.94%) and respiratory distress 308 (12.34%). Out of total, 1879 (75.3%) newborn were discharged successfully after treatment. 192 newborns were referred to higher centre for specialized care. 174 (7%) newborns died during the treatment. Conclusions: Neonatal period is a very crucial period for development of morbidity and mortality. SNCU with skilled staff can prevent the worst outcomes by early interventions.